Towards the Era of Society 5.0: Human Resources Management in Integrated Islamic Schools - Wisuda, Ani Himah; Fatimah, Siti (JURNAL AL-TANZIM, 2023)
This study aims to analyze the human resources management in Integrated Islamic Schools facing the era of society 5.0. To realize professional and adaptive human resources requires proper processes and management, one of which is by holding education and training programs aimed at preparing and developing the quality of human resources so that they are ready to face the times, such as the era of society 5.0. This study uses a qualitative method with a phenomenological approach. The data collection method used is the method of observation, interviews and documentation. Data analysis techniques include data collection, reduction, presentation, and verification. Checking the validity of the data includes increasing persistence and triangulation of sources and techniques. The study results show that with education and training that is packaged optimally and professionally, the human resources in integrated Islamic schools will be ready to face the era of society 5.0. This has implications for the importance of preparing human resources to be better prepared to face the times through various innovations and creations.